Impact of drying temperatures on drying behaviours, energy consumption and quality of purple sweet potato flour - Nguyen Minh Thuy; Le Huy Hiep; Ngo Van Tai; Huynh Thi Thu Huong; Vo Quang Minh (My University, 2022)
1Institute of Food and Biotechnology, Can Tho University, Vietnam 2School of Food Industry, King Mongkut’s Institute of Technology, Bangkok, Thailand 3College of Environment and Natural Resources, Can Tho University, Vietnam
Keywords: Freezing and Crystallization Processes